Layanan Garansi Toko pada Jual Beli Smartphone Bekas di Kota Palangka Raya - laili wahyunita (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
Guarantee is a form of service provided by sellers to consumers as a fulfillment of consumer rights, it is the right to obtain goods in accordance with the exchange the rate issued. This research aims to 1) the contract in store guarantee; 2) the implementation of store guarantee service procedure. This research is an empirical legal research with a socio - legal approach, and the method of data collection using interviews, observation, and documentation. The results showed that the contract agreed upon between the shop and the consumer regarding the application for a shop guarantee was the khiyar requirements and khiyar albi contracts. The guarantee application is made by coming directly to the store with a proof of purchase and a guarantee card. The implementation of store guarantee service procedures on the sale and purchase of second smartphones in Palangka Raya city has been carried out and fulfilled by several consumers, but from 9 (nine) consumers, there are 3 (three) consumers who experience cases of not being consumers and losses. There are 2 (two) smartphone sales shops that do not carry out their responsibilities to consumers as agreed.